Brassinosteroids promote development of rice pollen grains and seeds by triggering expression of Carbon Starved Anther, a MYB domain protein. (11th April 2015) - Zhu, Xiaolei; Liang, Wanqi; Cui, Xiao; Chen, Mingjiao; Yin, Changsong; Luo, Zhijing; Zhu, Jiaying; Lucas, William J.; Wang, Zhiyong; Zhang, Dabing
Summary Transport of photoassimilates from leaf tissues (source regions) to the sink organs is essential for plant development. Here, we show that a phytohormone, the brassinosteroids (BRs) promotes pollen and seed development in rice by directly promoting expression of Carbon Starved Anther (CSA) which encodes a MYB domain protein. Over‐expression of the BR‐synthesis gene D11 or a BR‐signaling factor OsBZR1 results in higher sugar accumulation in developing anthers and seeds, as well as higher grain yield compared with control non‐transgenic plants. Conversely, knockdown of D11 or OsBZR1 expression causes defective pollen maturation and reduced seed size and weight, with less accumulation of starch in comparison with the control. Mechanically, OsBZR1 directly promotes CSA expression and CSA directly triggers expression of sugar partitioning and metabolic genes during pollen and seed development. These findings provide insight into how BRs enhance plant reproduction and grain yield in an important agricultural crop.